Book Markets in Europe: Facing the Challenges of the Digital Single Market - Jedrzej Maciejewski (Comparative Economic Research. Central and Eastern Europe, 2019)
The aim of this article is to identify the challenges created by digitalization and the Digital Single Market for book markets in Europe. The research questions are, on the one hand, related to the nature of these challenges and the impact they have on European book markets, and on the other hand, the impact of the activities of EU institutions. This leads to the hypothesis that the digitization challenges that the book markets in Europe are facing are of a technological, economic, legal, political and judicial nature. Therefore, the key research method will be an analysis of these challenges and the (re)actions (under)taken by EU institutions. The book market in Europe is characterized by diversity and fragmentation in comparison with, for example, the American market, and is losing its share in the global book market with the development of book markets in emerging markets. Over the last decade, it shrank between 2008 and 2013 and started to rise again after 2014. In contrast to the European book market, the Polish book market is gradually decreasing. The e-book market, which developed dynamically between 2009 and 2014 (often at the expense of paper books), reached the level of about 6-7% of the entire book market in Europe. To meet the challenges of the ongoing digitization, the European Union has started to implement the Digital Single Market Strategy, which also affects the European book market through the directives and regulations adopted as part of the Strategy. European copyright law, by introducing exceptions and limitations, implemented to varying degrees in individual member states, affects the business models of European publishers. In addition, the activities of authors and publishers is influenced by the case law of the Court of Justice of the European Union (CJEU). Therefore, EU institutions, through the directive on copyright in the Digital Single Market, are trying to create an appropriate legal framework for out-of-commerce works or confirm the right to fair compensation for publishers. A separate issue remains e-lending, which is related to the possibility of borrowing e-books. The development of the e-book market was limited by different VAT rates of print and digital books, which was finally resolved by the European Par liament and the Council in 2017-2018. European institutions have an impact on the book market in Europe, where the European Commission has recently been trying to solve problems resulting from the interpretation of existing directives by the CJEU.
Keywords: K24; L86; O34; Z11; 330; book market; publishers; e-books; European Union; EU law; Digital Single Market; copyright; out-of-commerce works; e-lending; fair compensation; taxation